Raiva bovina na área de impacto da hidrelétrica de Aimorés, Minas Gerais, Brasil. - Michael Laurence Zini Lise (2005)
This research had the aim to evaluate the occurrence of rabies in animals from 1976 to 2004, examining the epidemic of rabies in cattle in 1965 and analyze the environmental impacts anticipated with the construction and operation of Hydroelectric Aimorés - UHEA could favor the occurrence epidemics of rabies in cattle in the counties of Aimorés, Ituela and Sunshine. Information on the occurrence of rabies in the records were obtained from laboratories of the Center for Zoonosis Control from the municipal government of Belo Horizonte - CCZ and the Instituto Mineiro de Agropecuária - IMA, autarchy linked to the Secretary of Agriculture of Minas Gerais. To determine Scores Occupation Agricultural Area Agricultural Censuses from 1950 to 1996 prepared by IBGE. The analysis on the impact of the flood of 31km2 was performed with visits in all municipalities in the area and with data from the environmental impact report produced by Companhia Energetica de Minas Gerais (CEMIG) - 1998. From 1976 to 2004, were sent 83 samples of brain tissue from animals suspected of rabies to laboratory confirmation, 61 cattle of which were positive 41amostras. The results on land use revealed that during the 1960s. The effect of beef has tripled in three decades from 21,468 in 1950, 45,006 in 1960 and 63,323 cattle in 1970. The areas occupied by lake, canal water supply, power house and other facilities Aimorés Hydropower Plant will be reduced and probably will not have significant consequences for the occurrence of an epidemic of rabies in cattle